Upaya Meningkatkan Kualitas Pembelajan PKN Menggunakan Model Kooperatif Tipe TGT (Teams Games Tournament) Berbantuan Multi Media di Kelas 3 SD Negeri 06 Luhak Nan Duo Kabupaten Pasaman Barat - Sari Kusuma; Yopita Anda Resta (Kampus Akademik Publiser, 2023)
Reflection with collaborators revealed that in Civic Education lessons in Grade III at SD Negeri 06 Luhak Nan Duo, teachers did not use methods that maximized the use of media, and students were not active in learning, resulting in suboptimal learning outcomes in Civic Education lessons. Based on observations, 58.4% (10 out of 24 students) did not achieve the minimum passing grade of 75. To overcome this, the researcher chose a multimedia-assisted Teams Games Tournament cooperative learning model. The purpose of this study was to improve the quality of civic education learning, which was summarized in the teachers' skills in managing the class, student activities in learning, and student learning outcomes. This classroom action research was conducted in 3 cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The data sources were teachers and 24 third-grade students at SD Negeri Negei 06 Luhak Nan Duo. Data collection techniques included tests and non-tests, as well as quantitative and qualitative analysis. The results showed that the teachers' skills in managing the class in cycle I were categorized as good, while those in cycles II and III were categorized as very good. Student activities in cycle I were categorized as good, while those in cycles II and III were categorized as very good. The results of cognitive learning showed that the classical mastery in cycle I was 72.7%, in cycle II was 90.75%, and in cycle III was 100%. Character assessment results for cycle I were categorized as good, while cycles II and III were categorized as very good.